Management of long span partially edentulous maxilla with fixed removable denture prosthesis - Mahilan I Jeyavalan; M Narasimman; C J Venkatakrishnan; M Philip Jacob (Wolters Kluwer Medknow Publications, 2012)
Restoration of a long span partially edentulous maxilla with tooth supported prosthesis is challenging because of inherent anatomic limitations and unfavourable biomechanics present after the loss of teeth. A tooth supported fixed-removable prosthesis is a treatment option for restoration of such long span partially edentulous maxillary arches. This prosthesis meets the requirements for esthetics, phonetics, comfort, and hygiene, as well as favourable biomechanical stress distribution to the remaining natural tooth abutments. This article presents a procedure for fabrication of a fixed-removable prosthesis that has cement-retained custom cast bar metal substructure and a ball attachment retained removable superstructure prosthesis.